Product Liability - جودانه, د.بن عیسی; عرفة, أ.أحمد (Dirasat in Economics and Business, 1982)
Rocent articles in various management and marketing journals have been dealing with the subject of product liability and its impact in innovation and manufacturer's behaviour. Related arguments varied from those In favour of free enterprise system, counting on Competition to sort our possible abuses of product safety and requirements, to those who maintain that consumers are best served under certain protective measures. While governments and their related institutionds in the industrialised nations tend to place strict liability on manufacturers, one sees almost nothing done about consumers in The emerging nations. On the contrary, governments in the developing countries tend to protect national industries against both domestic and foreign competition. Consequently, consumers in these nations have to put up with certain difficulties and restrictions different from those prevalent in the industrialised nations. This article attempts to examine the various dimensions of product liability, the way the subject has been looked at and tackled in the industrialised nations. Certain problems related to product liability in the emerging nations arise from a situation where producers of various imported products are not personally present in the markets; consequently, consumers complaints and court procedures are hindered. Our conclusions put forward certain strategic options for the emerging nations to follow if consumers' interests in these nations are to be satisfied.